Polarizing membrane manufacturing method and polarizing film manufacturing method

JP2025001759APending Publication Date: 2025-01-09NITTO DENKO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023101411
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2025-01-09

AI Technical Summary

Benefits of technology

【0010】 本発明の偏光膜の製造方法は、従前の偏光膜の製造方法と異なり、水を含有する延伸ポリビニルアルコール系フィルムに、当該延伸ポリビニルアルコール系フィルムの水分率が特定量範囲である状態で、水溶性の化合物を含む液体を塗布する工程を施して、特定の厚みである塗布液膜を有する延伸ポリビニルアルコール系フィルムを製造する工程を含むことから、水溶性の成分が偏光膜に析出なく含侵できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001759000001
    Figure 2025001759000001
Patent Text Reader

Abstract

To provide a polarizing membrane manufacturing method that allows a polarizing membrane to be impregnated with a water soluble component without precipitation.SOLUTION: A polarizing membrane manufacturing method includes steps of: (I) applying, while conveying a PVA-based film in a longitudinal direction, a cleaning step after applying at least stretching and dyeing steps, and manufacturing a stretching PVA-based film containing water; (II) applying a liquid including a water soluble compound to the obtained stretching PVA-based film containing the water in a state where a water content of the stretching PVA-based film is x wt.% (40≥x≥1.1*a thickness of the stretching PVA-based film (μm)), and manufacturing a stretching PVA-based film having a coating liquid membrane in which the thickness is 0.3 μm or more, and less than 2.2 μm; and (III) drying the obtained stretching PVA-based film having the coating liquid membrane, and manufacturing a polarizing membrane.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a polarizing membrane and a method for producing a polarizing film. [Background technology]

[0002] Conventionally, a dyed polyvinyl alcohol film (containing a dichroic substance such as iodine or a dichroic dye) has been used as a polarizing film (polarizer) for use in various image display devices such as liquid crystal display devices and organic EL display devices, because it has both high transmittance and high polarization degree. The polarizing film is produced by subjecting a polyvinyl alcohol film to various treatments such as dyeing, crosslinking, stretching, etc. in a bath (treatment bath), and then drying the film. The polarizing film is usually used as a polarizing film (polarizing plate) in which a protective film such as triacetyl cellulose is attached to one or both sides of the polarizing film using an adhesive.

[0003] As a method for producing a polarizing film, for example, Patent Documents 1 and 2 disclose a method for improving the durability of a polarizing film by adding a water-soluble component such as a metal salt containing zinc, copper, aluminum, etc. to a treatment bath to cause the polarizing film to contain the component. Patent Documents 3 and 4 disclose a method for producing a polarizing film by adding a water-soluble component such as an organic titanium compound to a treatment bath. Patent Document 5 discloses that a polarizing film with few optical defects can be obtained by a production method in which a cleaning solution is applied to a raw film by a coating roll in a cleaning process. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2016 / 117659 [Patent Document 2] JP 2006-047978 A [Patent Document 3] JP 2008-46257 A [Patent Document 4] Japanese Patent Application Publication No. 6-172554 [Patent Document 5] Patent Publication No. 2021-9203 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the methods for producing polarizing films of Patent Documents 1 to 4, when the above-mentioned components are added to the treatment bath, there are problems such as the amount of the components to be used being enormous, and the need for waste liquid treatment of the treatment liquid, etc. Moreover, the method specifically described in Patent Document 5 aims to clean the surface of the raw film roll with a cleaning liquid, and does not involve impregnating the raw film roll with the components of the cleaning liquid.

[0006] In view of the above circumstances, an object of the present invention is to provide a method for producing a polarizing film, which allows a water-soluble component to be impregnated into the polarizing film without causing precipitation.

[0007] Another object of the present invention is to provide a method for producing a polarizing film using the polarizing film obtained by the above-mentioned method for producing a polarizing film. [Means for solving the problem]

[0008] That is, the present invention relates to a method for producing a polarizing film, the method including: a step (I) of producing a water-containing stretched polyvinyl alcohol-based film by at least performing a stretching and dyeing step while transporting a polyvinyl alcohol-based film in the longitudinal direction, and then performing a washing step; a step (II) of coating the obtained water-containing stretched polyvinyl alcohol-based film with a liquid containing a water-soluble compound while the stretched polyvinyl alcohol-based film has a moisture content of x weight % (40≧x≧1.1×thickness of stretched polyvinyl alcohol-based film (μm)), thereby producing a stretched polyvinyl alcohol-based film having a coating liquid film with a thickness of 0.3 μm or more and 2.2 μm or less; and a step (III) of drying the obtained stretched polyvinyl alcohol-based film having the coating liquid film, thereby producing a polarizing film.

[0009] The present invention also relates to a method for producing a polarizing film, comprising a step of laminating a transparent protective film via an adhesive layer to at least one surface of the polarizing film obtained by the method for producing a polarizing film. Effect of the Invention

[0010] The method for producing a polarizing film of the present invention is different from conventional methods for producing polarizing films in that it includes a step of applying a liquid containing a water-soluble compound to a stretched polyvinyl alcohol-based film containing water, while the stretched polyvinyl alcohol-based film has a moisture content in a specific range, to produce a stretched polyvinyl alcohol-based film having a coating liquid film with a specific thickness, thereby allowing the water-soluble component to be impregnated into the polarizing film without precipitation.

[0011] <Method of manufacturing polarizing film> The method for producing a polarizing film of the present invention includes the steps of: (I) producing a water-containing stretched polyvinyl alcohol-based film by at least performing a stretching and dyeing step while transporting a polyvinyl alcohol-based film in the longitudinal direction, and then performing a washing step; (II) producing a stretched polyvinyl alcohol-based film having a coating liquid film with a thickness of 0.3 μm or more and 2.2 μm or less by performing a step of coating the stretched polyvinyl alcohol-based film having a coating liquid film with a thickness of 0.3 μm or more and 2.2 μm or less, while the stretched polyvinyl alcohol-based film having the coating liquid film is subjected to a drying step to produce a polarizing film.

[0012] <Step (I) of Producing a Water-Containing Stretched Polyvinyl Alcohol Film> In the step (I) of producing the water-containing stretched polyvinyl alcohol film, the polyvinyl alcohol film is subjected to at least the steps of stretching and dyeing while being transported in the longitudinal direction, and then to a washing step to produce a water-containing stretched polyvinyl alcohol film. In addition to the steps of stretching and dyeing, a swelling step and a crosslinking step may also be performed.

[0013] The polyvinyl alcohol (PVA) film can be used without any particular limitation as long as it has transparency in the visible light region and disperses and adsorbs dichroic substances such as iodine and dichroic dyes. In addition, the PVA film usually used as a raw sheet preferably has a thickness of about 1 to 100 μm, more preferably about 1 to 50 μm, and preferably has a width of about 100 to 5000 mm.

[0014] The material of the polyvinyl alcohol-based film includes polyvinyl alcohol or its derivatives. Examples of the polyvinyl alcohol derivatives include polyvinyl formal, polyvinyl acetal, olefins such as ethylene and propylene, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid, and their alkyl esters, modified with acrylamide, and the like. The polyvinyl alcohol preferably has an average degree of polymerization of about 100 to 10,000, more preferably about 1,000 to 10,000, and even more preferably about 1,500 to 4,500. The polyvinyl alcohol preferably has a saponification degree of about 80 to 100 mol%, and more preferably about 95 mol% to 99.95 mol. The average degree of polymerization and the saponification degree can be determined in accordance with JIS K 6726.

[0015] The polyvinyl alcohol-based film may contain additives such as plasticizers and surfactants. Examples of the plasticizers include polyols and condensates thereof, such as glycerin, diglycerin, triglycerin, ethylene glycol, propylene glycol, and polyethylene glycol. The amount of the additives used is not particularly limited, but is preferably about 20% by weight or less in the polyvinyl alcohol-based film.

[0016] The swelling step (hereinafter also referred to as the swelling step) is a treatment step in which the polyvinyl alcohol-based film is immersed in a swelling bath, which can remove dirt and blocking agents from the surface of the polyvinyl alcohol-based film, and can suppress uneven dyeing by swelling the polyvinyl alcohol-based film. The swelling bath generally uses a medium whose main component is water, distilled water, pure water, or the like. The swelling bath may contain surfactants, alcohol, and the like, as appropriate, according to a conventional method.

[0017] The temperature of the swelling bath is preferably about 10 to 60° C., and more preferably about 15 to 45° C. The immersion time in the swelling bath cannot be determined in general because the degree of swelling of the polyvinyl alcohol film is affected by the temperature of the swelling bath, but is preferably about 5 to 300 seconds, and more preferably about 10 to 200 seconds. The swelling step may be carried out only once, or may be carried out multiple times as necessary.

[0018] The dyeing step (hereinafter also referred to as the dyeing step) is a treatment step of immersing the polyvinyl alcohol-based film in a dye bath, and a dichroic substance such as iodine or a dichroic dye can be adsorbed and oriented in the polyvinyl alcohol-based film. The dyeing solution is usually preferably an aqueous iodine solution, and contains iodine and an iodide as a dissolution aid. Examples of the iodide include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide. Among these, potassium iodide is preferred.

[0019] The concentration of iodine in the dye bath is preferably about 0.01 to 1% by weight, more preferably about 0.02 to 0.5% by weight, and the concentration of iodide in the dye bath is preferably about 0.01 to 10% by weight, more preferably about 0.05 to 5% by weight.

[0020] The temperature of the dye bath is preferably about 10 to 50° C., and more preferably about 15 to 45° C. The immersion time in the dye bath cannot be determined in general because the degree of dyeing of the polyvinyl alcohol film is affected by the temperature of the dye bath, but is preferably about 10 to 300 seconds, and more preferably about 20 to 240 seconds. The dyeing step may be carried out only once, or may be carried out multiple times as necessary.

[0021] The above-mentioned crosslinking step (hereinafter also referred to as the crosslinking step) is a treatment step in which the polyvinyl alcohol-based film dyed in the dyeing step is immersed in a treatment bath (crosslinking bath) containing a boron compound, and the polyvinyl alcohol-based film is crosslinked by the boron compound, so that iodine molecules or dye molecules can be adsorbed to the crosslinked structure. Examples of the boron compound include boric acid, borate salts, and borax. The crosslinking bath is generally an aqueous solution, but may also be, for example, a mixed solution of water and an organic solvent miscible with water. The crosslinking bath may also contain an iodide such as potassium iodide.

[0022] The concentration of the boron compound in the crosslinking bath is preferably about 1 to 15% by weight, more preferably about 1.5 to 10% by weight, and even more preferably about 2 to 5% by weight. When an iodide such as potassium iodide is used in the crosslinking bath, the concentration of the iodide such as potassium iodide in the crosslinking bath is preferably about 1 to 15% by weight, and even more preferably about 1.5 to 10% by weight.

[0023] The temperature of the crosslinking bath is preferably about 20 to 70° C., and more preferably about 30 to 60° C. The immersion time in the crosslinking bath cannot be determined in general because the degree of crosslinking of the polyvinyl alcohol film is affected by the temperature of the crosslinking bath, but is preferably about 5 to 300 seconds, and more preferably about 10 to 200 seconds. The crosslinking step may be carried out only once, or may be carried out multiple times as necessary.

[0024] The stretching step (hereinafter also referred to as the stretching step) is a treatment step in which the polyvinyl alcohol-based film is stretched at least in one direction to a predetermined magnification. In general, the polyvinyl alcohol-based film is uniaxially stretched in the conveying direction (longitudinal direction). The stretching method is not particularly limited, and either a wet stretching method or a dry stretching method can be used. The stretching step may be carried out only once, or may be carried out multiple times as necessary. The stretching step may be carried out at any stage in the production of the polarizing film.

[0025] The treatment bath (stretching bath) in the wet stretching method can generally use a solvent such as water or a mixed solution of water and an organic solvent miscible with water. The stretching bath can contain an iodide such as potassium iodide. When an iodide such as potassium iodide is used in the stretching bath, the concentration of the iodide such as potassium iodide in the stretching bath is preferably about 1 to 15% by weight, more preferably about 2 to 10% by weight. The treatment bath (stretching bath) can also contain the boron compound in order to improve the degree of crosslinking. In this case, the concentration of the boron compound in the stretching bath is preferably about 1 to 15% by weight, more preferably about 1.5 to 10% by weight.

[0026] The temperature of the stretching bath is preferably about 25 to 80° C., more preferably about 40 to 75° C. The immersion time in the stretching bath cannot be generally determined because the degree of stretching of the polyvinyl alcohol film is affected by the temperature of the stretching bath, but is preferably about 10 to 800 seconds, more preferably about 30 to 500 seconds. The stretching treatment in the wet stretching method may be performed together with one or more of the dyeing step, the crosslinking step, the swelling step described later, and the washing step described later.

[0027] Examples of the dry stretching method include a roll-to-roll stretching method, a heated roll stretching method, a compression stretching method, etc. The dry stretching method may be carried out together with a drying step described later.

[0028] The total stretching ratio (cumulative stretching ratio) applied to the polyvinyl alcohol film can be appropriately set depending on the purpose, but is preferably about 2 to 7 times, more preferably about 3 to 6.8 times, and even more preferably about 3.5 to 6.5 times.

[0029] The above-mentioned washing step (hereinafter also referred to as the washing step) is a treatment step in which the polyvinyl alcohol-based film is immersed in a washing bath, and foreign matter remaining on the surface of the polyvinyl alcohol-based film can be removed. The washing bath generally uses a medium mainly composed of water, such as water, distilled water, or pure water. An iodide such as potassium iodide can be used in the washing bath, and in this case, the concentration of the iodide such as potassium iodide in the washing bath is preferably about 1 to 10% by weight, more preferably about 2 to 4% by weight, and even more preferably about 1.6 to 3.8% by weight.

[0030] The temperature of the cleaning bath is preferably about 5 to 50° C., more preferably about 10 to 40° C., and even more preferably about 15 to 35° C. The immersion time in the cleaning bath cannot be determined in general because the degree of cleaning of the polyvinyl alcohol film is affected by the temperature of the cleaning bath, but is preferably about 1 to 100 seconds, more preferably about 2 to 50 seconds, and even more preferably about 3 to 20 seconds. The swelling step may be carried out only once, or may be carried out multiple times as necessary.

[0031] Furthermore, each treatment bath in the swelling step, the dyeing step, the crosslinking step, the stretching step and the washing step may contain additives such as zinc salts, pH adjusters, pH buffers and other salts. Examples of the zinc salts include zinc halides such as zinc chloride and zinc iodide; inorganic zinc salts such as zinc sulfate and zinc acetate. Examples of the pH adjusters include strong acids such as hydrochloric acid, sulfuric acid and nitric acid, and strong bases such as sodium hydroxide and potassium hydroxide. Examples of the pH buffers include carboxylic acids such as acetic acid, oxalic acid and citric acid and their salts, and inorganic weak acids such as phosphoric acid and carbonic acid and their salts. Examples of the other salts include chlorides such as sodium chloride, potassium chloride and barium chloride, nitrates such as sodium nitrate and potassium nitrate, sulfates such as sodium sulfate and potassium sulfate, and salts of alkali metals and alkaline earth metals.

[0032] <Step (II) of Producing a Stretched Polyvinyl Alcohol Film Having a Coating Liquid Film> In the step (II) of producing the stretched polyvinyl alcohol film having the coating liquid film, a liquid containing a water-soluble compound is applied to the stretched polyvinyl alcohol film containing water obtained while the stretched polyvinyl alcohol film has a moisture content of x% by weight (40≧x≧1.1×thickness of the stretched polyvinyl alcohol film (μm)), to produce a stretched polyvinyl alcohol film having a coating liquid film having a thickness of 0.3 μm to 2.2 μm. The water-soluble compound is one having a solubility of 1 g or more in 100 g of water at 25° C. The liquid containing the water-soluble compound is a liquid for impregnating the stretched polyvinyl alcohol film with the water-soluble compound, and is not a liquid (cleaning liquid) intended for cleaning the stretched polyvinyl alcohol film.

[0033] In the step (II), if x exceeds 40, wrinkles are likely to occur during transport, making it difficult to transport normally. If x is smaller than 1.1 × the thickness (μm) of the stretched polyvinyl alcohol film, the polarizer is not sufficiently impregnated with the water-soluble component, and the water-soluble component precipitates on the surface of the polarizing film. The moisture content can be adjusted by adjusting the temperature of the cleaning bath and the degree of draining.

[0034] Examples of the water-soluble compound include the above-mentioned iodides, the above-mentioned boron compounds, the above-mentioned zinc salts, the above-mentioned pH adjusters, the above-mentioned pH buffers, the above-mentioned other salts, as well as compounds having a radical scavenging function, compounds having a crosslinking function, compounds having a plasticity imparting function, dye compounds, etc. The water-soluble compounds may be used alone or in combination of two or more kinds.

[0035] Examples of the compound having a radical scavenging function, from the viewpoint of suppressing a decrease in the single-unit transmittance and an increase in the single-unit hue b value of the polarizing film in a high-temperature environment, include hindered phenol-based, hindered amine-based, phosphorus-based, sulfur-based, benzotriazole-based, benzophenone-based, hydroxylamine-based, salicylic acid ester-based, and triazine-based compounds.

[0036] The compound having a crosslinking function reacts with the hydroxyl group of the polyvinyl alcohol of the polarizing film to form a crosslinked structure, and can improve the durability of the polarizing film against humidification. From the viewpoint of improving the durability against humidification, examples of the compound having a crosslinking function include organic compounds having an isocyanate group, an isocyanate-derived functional group, an epoxy group, a carbonyl group, an aziridine ring, a vinyl ether group, a vinyl sulfone group, and an oxazoline group, as well as organic titanium compounds (titanium alkoxides, titanium chelates, titanium chelate ammonium salts, titanium chelate acylates, etc.).

[0037] The compound having a plasticity imparting function can impart plasticity to the polarizing film, thereby reducing quality defects such as dents caused by the pressing force. Examples of the compound having a plasticity imparting function include ethylene glycol, polyethylene glycol, other ethylene glycol derivatives, glycerin, etc.

[0038] The dye-based compound can impart properties such as hue adjustment to the polarizing film and pattern printing, etc. Examples of the dye-based compound include azo compounds, anthraquinone-based compounds, and quinophthalone-based compounds.

[0039] As the coating method in the step of coating the liquid containing the water-soluble compound, a conventional coating method can be applied, and examples of such coating methods include gravure coating, roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, and knife coating (comma coating, etc.). Among these, gravure coating is preferred from the viewpoint of the target coating thickness and processability. In the gravure coating method, it is preferable that the rotation direction of the gravure roll and the transport direction of the stretched polyvinyl alcohol film are opposite to each other. In this case, a stable coating film can be formed. In addition, various patterns can be formed on the surface of the gravure roll, and for example, a honeycomb mesh pattern, a trapezoid pattern, a lattice pattern, a pyramid pattern, or a diagonal line pattern can be formed. Any pattern can be selected, and in the case of a honeycomb mesh pattern, from the viewpoint of the target coating thickness, the cell volume is 1 to 10 cm. 3 / m 2 It is preferable that the length is 3 to 8 cm. 3 / m 2 It is preferable that the cell line number per inch of the roll is 200 to 3000 lines / inch. It is also preferable that the ratio of the rotation speed of the gravure roll to the traveling speed of the stretched polyvinyl alcohol film is 100 to 300%. The coating surface may be one side or both sides.

[0040] The liquid containing the water-soluble compound cannot be determined in general because it is affected by the application (coating) format described above. However, from the viewpoint of efficiently penetrating the water-soluble compound, the concentration of the water-soluble compound is preferably 0.1% by weight or more, and more preferably 1.0% by weight or more, and from the viewpoint of preventing quality defects due to precipitation of the water-soluble compound, the concentration is preferably 30% by weight or less, and more preferably 20% by weight or less.

[0041] Examples of the liquid solvent include water; water-soluble solvents such as methanol, ethanol, ethylene glycol, polyethylene glycol, other ethylene glycol derivatives, glycerin, and dimethyl sulfoxide.

[0042] The stretched polyvinyl alcohol-based film having the coating liquid film has a coating liquid film thickness of 0.3 μm or more and 2.2 μm or less. From the viewpoint of the stability of the coating liquid film, the coating liquid film thickness is preferably 0.5 μm or more, more preferably 0.7 μm or more, and from the viewpoint of the impregnation of the coating liquid components, the coating liquid film thickness is preferably 2.0 μm or less, more preferably 1.5 μm or less.

[0043] From the viewpoint of producing a polarizing film having uniform properties, the stretched polyvinyl alcohol film having the coating liquid film preferably has coating unevenness of less than 0.1 μm, and more preferably 0.08 μm or less.

[0044] <Step (III) of Producing Polarizing Film> In the step (III) of producing the polarizing film, the stretched polyvinyl alcohol film having the coating liquid film thus obtained is subjected to a drying step to produce the polarizing film.

[0045] The drying step (hereinafter also referred to as drying step) is a step of drying the stretched polyvinyl alcohol film having the coating liquid film obtained above to obtain a polarizing film, and a polarizing film having a desired moisture content can be obtained by drying. The drying is performed by any appropriate method, and examples of the method include natural drying, air drying, and heat drying.

[0046] The drying temperature is preferably about 20 to 150° C., and more preferably about 25 to 100° C. The drying time cannot be determined in general because the degree of drying of the polarizing film is affected by the drying temperature, but is preferably about 10 to 600 seconds, and more preferably about 30 to 300 seconds. The drying step may be carried out only once, or may be carried out multiple times as necessary.

[0047] In the step (III), the stretched polyvinyl alcohol film having the obtained coating liquid film is preferably subjected to a step of promoting the impregnation of the water-soluble compound and then a step of drying, from the viewpoint of the impregnation of the coating liquid components. Examples of the step of promoting the impregnation of the water-soluble compound include blowing a gas (air, nitrogen, etc.) onto the polarizing film, applying heat, and providing a sufficient air transport distance for impregnation. When blowing a gas onto the polarizing film, the wind speed is preferably about 0.5 to 5.0 m / s, and more preferably about 1.0 to 3.0 m / s. The temperature is preferably about 10 to 50°C, and more preferably about 15 to 30°C.

[0048] From the viewpoint of the impregnation of the coating liquid components, the step of promoting the impregnation of the water-soluble compound is preferably performed before the stretched polyvinyl alcohol film transported after the step of applying the liquid containing the water-soluble compound comes into contact with the next transport roll (guide roll or nip roll).

[0049] In the step (III), from the viewpoint of impregnation of the coating liquid components, it is preferable not to subject the stretched polyvinyl alcohol film having the coating liquid film to a step of draining the coating liquid film.

[0050] The polarizing film has a moisture content of preferably 10% by weight or more, more preferably 12% by weight or more, from the viewpoint of preventing quality defects such as dents due to loss of plasticity, and preferably 20% by weight or less, more preferably 16% by weight or less, from the viewpoint of improving optical properties such as the degree of polarization. In the case of a polarizing film having a thickness of about 8 μm or less, which will be described later, the moisture content of the polarizing film is preferably 2% by weight or more, more preferably 3% by weight or more, from the viewpoint of preventing quality defects such as dents due to loss of plasticity, and preferably 20% by weight or less, more preferably 10% by weight or less, from the viewpoint of improving optical properties such as the degree of polarization.

[0051] The thickness of the polarizing film is preferably about 1 to 30 μm, more preferably about 3 to 25 μm, and further preferably 5 to 20 μm. In particular, to obtain a polarizing film having a thickness of about 8 μm or less, the following method for producing a thin polarizing film can be applied, in which a laminate including a polyvinyl alcohol-based resin layer formed on a thermoplastic resin substrate is used as the polyvinyl alcohol-based film.

[0052] <Production method of polarizing film (thin polarizing film)> The method for producing a polarizing film (thin polarizing film) includes the steps of: preparing a laminate by forming a polyvinyl alcohol-based resin layer containing a polyvinyl alcohol-based resin on one side of a long thermoplastic resin substrate (I-0); transporting the obtained laminate in the longitudinal direction, and subjecting the laminate to at least an auxiliary air-stretching process, a dyeing process, and an underwater stretching process, followed by a washing process, to produce a laminate of stretched polyvinyl alcohol-based films containing water (I-1); The method includes a step (II-1) of applying a liquid containing a water-soluble compound to a laminate of stretched polyvinyl alcohol-based films while the moisture content of the stretched polyvinyl alcohol-based resin layer is x% by weight (40≧x≧1.1×thickness of stretched polyvinyl alcohol-based film (μm)) to produce a laminate of stretched polyvinyl alcohol-based films having a coating liquid film with a thickness of 0.3 μm to 2.2 μm, and a step (III-1) of drying the resulting laminate of stretched polyvinyl alcohol-based films having a coating liquid film to produce a polarizing film.

[0053] <Step (I-0) of preparing a laminate> In the step (I-0) of preparing a laminate, a polyvinyl alcohol-based resin layer containing a polyvinyl alcohol-based resin is formed on one side of a long thermoplastic resin substrate to prepare a laminate.

[0054] The laminate may be prepared by any suitable method, for example, by applying a coating liquid containing the PVA resin to the surface of the thermoplastic resin substrate and drying the coating liquid. The thickness of the thermoplastic resin substrate is preferably about 20 to 300 μm, more preferably about 50 to 200 μm. The thickness of the PVA resin layer is preferably about 3 to 40 μm, more preferably about 3 to 20 μm.

[0055] The thermoplastic resin substrate preferably has a water absorption rate of about 0.2% or more, more preferably about 0.3% or more, from the viewpoint of absorbing water to greatly reduce the stretching stress and being able to be stretched at a high ratio. On the other hand, the thermoplastic resin substrate preferably has a water absorption rate of about 3% or less, more preferably about 1% or less, from the viewpoint of preventing defects such as a significant decrease in the dimensional stability of the thermoplastic resin substrate and a deterioration in the appearance of the resulting polarizing film. The water absorption rate can be adjusted, for example, by introducing a modifying group into the constituent material of the thermoplastic resin substrate. The water absorption rate is a value determined in accordance with JIS K 7209.

[0056] The thermoplastic resin substrate preferably has a glass transition temperature (Tg) of about 120° C. or less from the viewpoint of ensuring sufficient stretchability of the laminate while suppressing crystallization of the PVA-based resin layer. Furthermore, in consideration of the plasticization of the thermoplastic resin substrate by water and the underwater stretching being performed well, the glass transition temperature (Tg) is more preferably about 100° C. or less, and even more preferably about 90° C. or less. On the other hand, the glass transition temperature of the thermoplastic resin substrate is preferably about 60° C. or more from the viewpoint of preventing defects such as deformation of the thermoplastic resin substrate when applying and drying a coating liquid and producing a good laminate. The glass transition temperature can be adjusted, for example, by introducing a modifying group into the constituent material of the thermoplastic resin substrate or by heating using a crystallizing material. The glass transition temperature (Tg) is a value determined in accordance with JIS K 7121.

[0057] Any suitable thermoplastic resin may be used as the constituent material of the thermoplastic resin substrate. Examples of the thermoplastic resin include ester resins such as polyethylene terephthalate resins, cycloolefin resins such as norbornene resins, olefin resins such as polypropylene, polyamide resins, polycarbonate resins, and copolymer resins thereof. Among these, norbornene resins and amorphous polyethylene terephthalate resins are preferred, and amorphous polyethylene terephthalate resins are preferably used because the thermoplastic resin substrate has excellent stretchability and crystallization during stretching can be suppressed. Examples of amorphous polyethylene terephthalate resins include copolymers containing isophthalic acid and / or cyclohexane dicarboxylic acid as dicarboxylic acids, and copolymers containing cyclohexane dimethanol or diethylene glycol as glycols.

[0058] The thermoplastic resin substrate may be subjected to a surface treatment (e.g., corona treatment, etc.) before forming the PVA-based resin layer, or an easy-adhesion layer may be formed on the thermoplastic resin substrate. By carrying out such treatment, the adhesion between the thermoplastic resin substrate and the PVA-based resin layer can be improved. In addition, the thermoplastic resin substrate may be stretched before forming the PVA-based resin layer.

[0059] The coating liquid is a solution in which a PVA-based resin is dissolved in a solvent. Examples of the solvent include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, and amines such as ethylenediamine and diethylenetriamine, with water being preferred. These can be used alone or in combination of two or more. The concentration of the PVA-based resin in the coating liquid is preferably about 3 to 20 parts by weight relative to 100 parts by weight of the solvent, from the viewpoint of forming a uniform coating film that is in close contact with the thermoplastic resin substrate.

[0060] The coating liquid preferably contains a halide from the viewpoint of improving the orientation of polyvinyl alcohol molecules by stretching. Any appropriate halide can be used as the halide, and examples thereof include iodide and sodium chloride. Examples of the iodide include potassium iodide, sodium iodide, and lithium iodide, and potassium iodide is preferred. The concentration of the halide in the coating liquid is preferably about 5 to 20 parts by weight, and more preferably about 10 to 15 parts by weight, based on 100 parts by weight of the PVA resin.

[0061] The coating liquid may contain additives, such as plasticizers, such as ethylene glycol and glycerin, and surfactants, such as nonionic surfactants.

[0062] The coating method of the coating liquid may be any appropriate method, such as roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, knife coating (comma coating, etc.), etc. The drying temperature of the coating liquid is preferably about 50° C. or higher.

[0063] <Step (I-1) of Producing a Laminate of Water-Containing Stretched Polyvinyl Alcohol Film> In the step (I-1) of producing the above-mentioned water-containing stretched polyvinyl alcohol-based film laminate, the obtained laminate is transported in the longitudinal direction and subjected to at least an auxiliary air-stretching process, a dyeing process, and an underwater stretching process, and then a washing process to produce a water-containing stretched polyvinyl alcohol-based film laminate.

[0064] In the auxiliary air-stretching process, the laminate can be stretched at a high ratio since the crystallization of the thermoplastic resin substrate can be suppressed. The stretching method in the auxiliary air-stretching process may be fixed-end stretching (e.g., a method of stretching using a tenter stretching machine) or free-end stretching (e.g., a method of uniaxially stretching the laminate by passing it between rolls having different peripheral speeds), but free-end stretching is preferred from the viewpoint of obtaining high optical properties.

[0065] The stretching ratio in the auxiliary in-air stretching step is preferably about 2 to 3.5. The auxiliary in-air stretching step may be performed in one stage or in multiple stages. When performed in multiple stages, the stretching ratio is the product of the stretching ratios in each stage.

[0066] The stretching temperature in the auxiliary air-stretching process can be set to any appropriate value depending on the material forming the thermoplastic resin substrate, the stretching method, etc., and is, for example, preferably equal to or higher than the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably equal to or higher than the glass transition temperature (Tg) + 10° C., and even more preferably equal to or higher than the glass transition temperature (Tg) + 15° C. On the other hand, the upper limit of the stretching temperature is preferably about 170° C., from the viewpoint of suppressing rapid crystallization of the PVA-based resin and suppressing defects due to crystallization (for example, preventing the orientation of the PVA-based resin layer due to stretching).

[0067] If necessary, an insolubilization treatment step may be performed after the auxiliary air-stretching treatment step and before the dyeing treatment step or the underwater stretching treatment step. The insolubilization treatment step is typically performed by immersing the PVA-based resin layer in an aqueous solution of boric acid. By performing the insolubilization treatment step, water resistance is imparted to the PVA-based resin layer, and it is possible to prevent a decrease in the orientation of PVA when immersed in water. The concentration of the aqueous solution of boric acid is preferably about 1 to 5 parts by weight relative to 100 parts by weight of water. The liquid temperature of the insolubilization bath is preferably about 20 to 50°C.

[0068] The dyeing process is carried out by dyeing the PVA-based resin layer with iodine. Examples of the adsorption method include a method of immersing the PVA-based resin layer (laminate) in a dyeing solution containing iodine, a method of applying the dyeing solution to the PVA-based resin layer, and a method of spraying the dyeing solution onto the PVA-based resin layer, and the like. The method of immersing the PVA-based resin layer (laminate) in a dyeing solution containing iodine is preferred.

[0069] The amount of iodine in the dye bath is preferably about 0.05 to 0.5 parts by weight relative to 100 parts by weight of water. In order to increase the solubility of iodine in water, it is preferable to mix the iodide in the iodine aqueous solution. The amount of iodide is preferably about 0.1 to 10 parts by weight, more preferably about 0.3 to 5 parts by weight, relative to 100 parts by weight of water. The liquid temperature of the dye bath is preferably about 20 to 50°C in order to suppress dissolution of the PVA resin. In addition, the immersion time is preferably about 5 seconds to 5 minutes, more preferably about 30 seconds to 90 seconds, from the viewpoint of ensuring the transmittance of the PVA resin layer. In order to obtain a polarizing film having good optical properties, the ratio of the contents of iodine and iodide in the iodine aqueous solution is preferably about 1:5 to 1:20, more preferably about 1:5 to 1:10.

[0070] If necessary, a crosslinking process may be performed after the dyeing process and before the underwater stretching process. The crosslinking process is typically performed by immersing the PVA resin layer in an aqueous boric acid solution. The crosslinking process imparts water resistance to the PVA resin layer, and prevents the orientation of the PVA from decreasing when the layer is immersed in high-temperature water in the subsequent underwater stretching process. The boric acid concentration of the aqueous boric acid solution is preferably about 1 to 5 parts by weight relative to 100 parts by weight of water. In addition, when the crosslinking process is performed, it is preferable to further add the iodide to the crosslinking bath. By adding the iodide, it is possible to suppress the elution of iodine adsorbed to the PVA resin layer. The amount of the iodide added is preferably about 1 to 5 parts by weight relative to 100 parts by weight of water. The liquid temperature of the crosslinking bath (aqueous boric acid solution) is preferably about 20 to 50°C.

[0071] The underwater stretching process is performed by immersing the laminate in a stretching bath. According to the underwater stretching process, stretching can be performed at a temperature lower than the glass transition temperature (typically about 80° C.) of the thermoplastic resin substrate or the PVA-based resin layer, and the PVA-based resin layer can be stretched at a high magnification while suppressing crystallization. The stretching method in the underwater stretching process may be fixed-end stretching (for example, a method of stretching using a tenter stretching machine) or free-end stretching (for example, a method of uniaxially stretching the laminate by passing it between rolls with different peripheral speeds), but free-end stretching is preferred from the viewpoint of obtaining high optical properties.

[0072] The underwater stretching step is preferably performed by immersing the laminate in an aqueous boric acid solution (stretching in an aqueous boric acid solution). By using an aqueous boric acid solution as the stretching bath, it is possible to impart to the PVA-based resin layer rigidity that can withstand the tension applied during stretching and water resistance that does not dissolve in water. The boric acid concentration of the aqueous boric acid solution is preferably 1 to 10 parts by weight, more preferably 2.5 to 6 parts by weight, per 100 parts by weight of water. In addition, an iodide may be blended into the stretching bath (aqueous boric acid solution). The liquid temperature of the stretching bath is preferably about 40 to 85°C, more preferably about 60 to 75°C. The immersion time of the laminate in the stretching bath is preferably about 15 seconds to 5 minutes.

[0073] The stretching ratio in the underwater stretching process is preferably about 1.5 times or more, and more preferably about 3 times or more.

[0074] The total stretching ratio of the laminate is preferably about 5 times or more, and more preferably about 5.5 times or more, relative to the original length of the laminate.

[0075] The washing treatment step is typically carried out by immersing the PVA-based resin layer in an aqueous solution of potassium iodide.

[0076] Furthermore, each treatment bath in the dyeing process, the underwater stretching process, the insolubilization process, the crosslinking process, and the washing process may contain additives such as zinc salts, pH adjusters, pH buffers, and other salts. Examples of the zinc salts include zinc halides such as zinc chloride and zinc iodide; inorganic zinc salts such as zinc sulfate and zinc acetate. Examples of the pH adjusters include strong acids such as hydrochloric acid, sulfuric acid, and nitric acid, and strong bases such as sodium hydroxide and potassium hydroxide. Examples of the pH buffers include carboxylic acids such as acetic acid, oxalic acid, and citric acid, and salts thereof, and inorganic weak acids such as phosphoric acid and carbonic acid, and salts thereof. Examples of the other salts include chlorides such as sodium chloride, potassium chloride, and barium chloride, nitrates such as sodium nitrate and potassium nitrate, sulfates such as sodium sulfate and potassium sulfate, and salts of alkali metals and alkaline earth metals.

[0077] <Step (II-1) of Producing a Laminate of Stretched Polyvinyl Alcohol Film Having a Coating Liquid Film> In the step (II-1) of producing a laminate of stretched polyvinyl alcohol-based films having the above-mentioned coating liquid film, a step of coating a liquid containing a water-soluble compound is carried out on the obtained laminate of stretched polyvinyl alcohol-based films containing water, in a state in which the moisture content of the stretched polyvinyl alcohol-based resin layer is x% by weight (40≧x≧1.1×thickness (μm) of the stretched polyvinyl alcohol-based film), to produce a laminate of stretched polyvinyl alcohol-based films having a coating liquid film having a thickness of 0.3 μm or more and 2.2 μm or less. In the step (II-1), all of the steps (II) of producing the stretched polyvinyl alcohol-based films having the above-mentioned coating liquid film can be applied. However, the liquid containing a water-soluble compound is applied (coated) to the surface of the stretched polyvinyl alcohol-based film.

[0078] <Process for producing polarizing film (III-1)> In the step (III-1) of producing the polarizing film, the laminate of the stretched polyvinyl alcohol film having the coating liquid film thus obtained is subjected to a drying treatment to produce the polarizing film. In the step (III-1), all of the steps (III) of producing the polarizing film described above can be applied.

[0079] The drying process is carried out by any appropriate method, and examples of the method include natural drying, air drying, and heat drying. The drying process may be carried out by zone heating in which the entire zone is heated, or by heating the transport roll (using a so-called heating roll). Drying using a heating roll efficiently suppresses heat curling of the laminate, making it possible to produce a polarizing film with excellent appearance, and since the laminate can be dried while being kept flat, it is possible to suppress not only curling but also wrinkles. In addition, from the viewpoint of improving the optical properties of the obtained polarizing film by shrinking the laminate in the width direction during the drying process, the shrinkage rate of the laminate in the width direction due to the drying process is preferably about 1 to 10%, more preferably about 2 to 8%.

[0080] Drying conditions can be controlled by adjusting the heating temperature of the transport rolls (temperature of the heating rolls), the number of heating rolls, contact time with the heating rolls, etc. The temperature of the heating rolls is preferably about 60 to 120°C, more preferably about 65 to 100°C, and even more preferably 70 to 80°C. From the viewpoint of satisfactorily increasing the crystallinity of the thermoplastic resin and satisfactorily suppressing curling, the number of transport rolls is usually about 2 to 40, preferably about 4 to 30. The contact time (total contact time) between the laminate and the heating rolls is preferably about 1 to 300 seconds, more preferably 1 to 20 seconds, and even more preferably 1 to 10 seconds.

[0081] The heating roll may be installed in a heating furnace or in a normal production line (under room temperature environment). It is preferably installed in a heating furnace equipped with a blowing means. By using drying with the heating roll and hot air drying in combination, it is possible to suppress a steep temperature change between the heating rolls, and it is possible to easily control the shrinkage in the width direction. The hot air drying temperature is preferably about 30 to 100°C. In addition, the hot air drying time is preferably about 1 to 300 seconds.

[0082] <Method of manufacturing polarizing film> The method for producing a polarizing film of the present invention includes a step of laminating a transparent protective film via an adhesive layer to at least one surface of the polarizing film obtained by the method for producing a polarizing film described above.

[0083] The transparent protective film is not particularly limited, and various transparent protective films used in polarizing films can be used. As a material constituting the transparent protective film, for example, a thermoplastic resin excellent in transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, etc. can be used. Examples of the thermoplastic resin include cellulose ester resins such as triacetyl cellulose, polyester resins such as polyethylene terephthalate and polyethylene naphthalate, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins such as nylon and aromatic polyamide, polyimide resins, polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins) having a cyclo or norbornene structure, polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. In addition, the transparent protective film can be a cured layer formed from a thermosetting resin or an ultraviolet curing resin such as a (meth)acrylic, urethane, acrylic urethane, epoxy, or silicone resin. Among these, cellulose ester resins, polycarbonate resins, (meth)acrylic resins, cyclic polyolefin resins, and polyester resins are preferred.

[0084] The thickness of the transparent protective film can be determined as appropriate, but generally, from the viewpoints of workability such as strength and handleability, thinness, etc., it is preferably about 1 to 500 μm, more preferably about 1 to 300 μm, and even more preferably about 5 to 100 μm.

[0085] When the transparent protective films are attached to both sides of the polarizing film, the transparent protective films on both sides may be the same or different.

[0086] The transparent protective film may be a retardation plate having a front retardation of 40 nm or more and / or a thickness retardation of 80 nm or more. The front retardation is usually controlled to be in the range of 40 to 200 nm, and the thickness retardation is usually controlled to be in the range of 80 to 300 nm. When a retardation plate is used as the transparent protective film, the retardation plate also functions as the transparent protective film, so that the film can be made thinner.

[0087] Examples of the retardation plate include a birefringent film obtained by uniaxial or biaxial stretching of a polymeric material, an oriented film of a liquid crystal polymer, and an oriented layer of a liquid crystal polymer supported by a film. The thickness of the retardation plate is not particularly limited, but is generally about 20 to 150 μm. The retardation plate may be used by laminating it to a transparent protective film that does not have a retardation.

[0088] The transparent protective film may contain any suitable additive, such as an ultraviolet absorbing agent, an antioxidant, a lubricant, a plasticizer, a release agent, a coloring inhibitor, a flame retardant, an antistatic agent, a pigment, or a colorant.

[0089] The surface of the transparent protective film to which the polarizing film is not attached may be provided with a functional layer such as a hard coat layer, an anti-reflection layer, an anti-sticking layer, a diffusion layer, an anti-glare layer, etc. The functional layer such as the hard coat layer, the anti-reflection layer, the anti-sticking layer, the diffusion layer, the anti-glare layer, etc. may be provided on the protective film itself, or may be provided separately from the protective film.

[0090] The polarizing film and the transparent protective film, or the polarizing film and the functional layer, are usually attached to each other via a pressure-sensitive adhesive layer or an adhesive layer.

[0091] As the adhesive forming the adhesive layer, various adhesives used in polarizing films can be used, and examples thereof include rubber-based adhesives, acrylic-based adhesives, silicone-based adhesives, urethane-based adhesives, vinyl alkyl ether-based adhesives, polyvinyl alcohol-based adhesives, polyvinyl porolidone-based adhesives, polyacrylamide-based adhesives, cellulose-based adhesives, etc. Among these, acrylic-based adhesives are preferred.

[0092] Examples of the method for forming the adhesive layer include a method in which the adhesive is applied to a release-treated separator or the like, dried to form an adhesive layer, and then transferred to a polarizing film or the like, or a method in which the adhesive is applied to a polarizing film or the like, dried to form an adhesive layer, etc. The thickness of the adhesive layer is not particularly limited and is, for example, about 1 to 100 μm, and preferably about 2 to 50 μm.

[0093] The adhesive for forming the adhesive layer may be any of various adhesives used in polarizing films, including, for example, isocyanate-based adhesives, polyvinyl alcohol-based adhesives, gelatin-based adhesives, vinyl latex-based adhesives, water-based polyesters, etc. These adhesives are usually used as aqueous solutions, and contain 0.5 to 60% by weight of solids.

[0094] In addition to the above, examples of the adhesive include active energy ray curable adhesives such as ultraviolet ray curable adhesives and electron beam curable adhesives. Examples of the active energy ray curable adhesives include (meth)acrylate adhesives. Examples of the curable components in the (meth)acrylate adhesives include compounds having a (meth)acryloyl group and compounds having a vinyl group. In addition, compounds having an epoxy group or an oxetanyl group can also be used as cationic polymerization curable adhesives. The compound having an epoxy group is not particularly limited as long as it has at least two epoxy groups in the molecule, and various commonly known curable epoxy compounds can be used.

[0095] The adhesive may be applied to either the transparent protective film side (or the functional layer side) or the polarizing film side, or may be applied to both. After lamination, a drying step is performed to form an adhesive layer consisting of a dried coating layer. After the drying step, ultraviolet rays or electron beams may be irradiated as necessary. The thickness of the adhesive layer is not particularly limited, and when a water-based adhesive or the like is used, it is preferably about 30 to 5000 nm, more preferably about 100 to 1000 nm, and when a UV-curable adhesive, an electron beam-curable adhesive, or the like is used, it is preferably about 0.1 to 100 μm, more preferably about 0.5 to 10 μm.

[0096] The transparent protective film and the polarizing film, or the polarizing film and the functional layer, may be laminated via an intervening layer such as a surface modification layer, an easy-adhesive layer, a blocking layer, or a refractive index adjustment layer.

[0097] Examples of the surface modification treatment for forming the surface modification layer include corona treatment, plasma treatment, primer treatment, and saponification treatment.

[0098] Examples of the adhesive that forms the easy-adhesion layer include forming materials containing various resins having a polyester skeleton, a polyether skeleton, a polycarbonate skeleton, a polyurethane skeleton, a silicone-based skeleton, a polyamide skeleton, a polyimide skeleton, a polyvinyl alcohol skeleton, etc. The easy-adhesion layer is usually provided in advance on a protective film, and the easy-adhesion layer side of the protective film and the polarizing film are laminated with the pressure-sensitive adhesive layer or the adhesive layer.

[0099] The blocking layer is a layer having a function of preventing impurities such as oligomers and ions eluted from a transparent protective film, etc. from migrating (penetrating) into the polarizing film. The blocking layer may be any layer that is transparent and can prevent impurities from eluting from a transparent protective film, etc., and examples of materials for forming the blocking layer include urethane prepolymer-based forming materials, cyanoacrylate-based forming materials, and epoxy-based forming materials.

[0100] The refractive index adjusting layer is a layer provided to suppress a decrease in transmittance caused by reflection between layers having different refractive indices such as the transparent protective film and a polarizing film, etc. Examples of the refractive index adjusting material forming the refractive index adjusting layer include forming agents containing various resins and additives such as silica-based, acrylic-based, acrylic-styrene-based, and melamine-based resins.

[0101] The polarizing film preferably has a polarization degree of 99.98% or more, and more preferably has a polarization degree of 99.99% or more. EXAMPLES

[0102] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples.

[0103] <Preparation of polarizing film> <Example 1> A polyvinyl alcohol film with an average degree of polymerization of 2,400, a degree of saponification of 99.9 mol%, and a thickness of 45 μm was prepared. The polyvinyl alcohol film was stretched 2.2 times in the conveying direction while swelling by immersing in a swelling bath (water bath) at 30° C. between rolls with different peripheral speed ratios (swelling step), and then stretched 3.3 times in the conveying direction based on the original polyvinyl alcohol film (polyvinyl alcohol film not stretched at all in the conveying direction) while dyeing by immersing in a dyeing bath (iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at 30° C. for 30 seconds while adjusting the iodine concentration so that the polarizing film has a predetermined transmittance (dyeing step). Next, the dyed polyvinyl alcohol film was immersed in a 40°C crosslinking bath (aqueous solution with a boric acid concentration of 3.5% by weight, a potassium iodide concentration of 3.0% by weight, and a zinc sulfate concentration of 3.6% by weight) for 28 seconds to be stretched in the conveying direction to 3.6 times the original polyvinyl alcohol film (crosslinking step).Furthermore, the obtained polyvinyl alcohol film was immersed in a 64°C stretching bath (aqueous solution with a boric acid concentration of 4.8% by weight, a potassium iodide concentration of 5.0% by weight, and a zinc sulfate concentration of 5.0% by weight) for 60 seconds to be stretched in the conveying direction to 6.0 times the original polyvinyl alcohol film (stretching step), and then immersed in a 29°C washing bath (potassium iodide concentration of 2.3% by weight) for 10 seconds (washing step). Furthermore, the stretched polyvinyl alcohol film (thickness 18 μm) obtained after washing was gravure coated (conditions: honeycomb mesh pattern, 700 [lines / inch], cell volume 5 [cm]) with a moisture content of 20.5 wt%. 3 / m 2 ], gravure rotation speed ratio: 100%, the rotation direction of the gravure roll is opposite to the transport direction of the stretched polyvinyl alcohol film), an aqueous solution of potassium iodide with a concentration of 4.0% by weight was applied to the film to a thickness of 0.81 μm. The film was then dried at 40° C. for 30 seconds to prepare a polarizing film.

[0104] <Method for measuring moisture content (weight%) of stretched polyvinyl alcohol film> About 0.2 g of the stretched polyvinyl alcohol film was weighed out and dried at 120° C. for 2 hours. The weight after drying was measured, and the moisture content (W) of the stretched polyvinyl alcohol film was calculated according to the following formula. Moisture content of stretched polyvinyl alcohol film W (wt%) = {(M 0 -M 1 ) / M 0}×100 M 0 : Measured weight of stretched polyvinyl alcohol film (g) M 1 Weight (g) of stretched polyvinyl alcohol film after drying at 120°C for 2 hours

[0105] <(A) Measurement method for coating liquid film> The thickness of the coating liquid film was measured using a spectroscopic interference film thickness meter immediately after the coating process. The measurement was performed within 1 to 2 seconds from coating.

[0106] The stretched polyvinyl alcohol film and the polarizing film obtained above were used to carry out the following evaluations. The results are shown in Table 1.

[0107] <(B) Evaluation of coating unevenness> The coating thickness was calculated according to (A) at six points within an area of ​​100 x 100 mm, and the coating unevenness was calculated according to the following formula. It is preferable that the coating unevenness is less than 0.1 μm. Coating unevenness (μm)=AB A: The maximum film thickness value (μm) among the six points B: The smallest film thickness value (μm) among the six points

[0108] <(C) Evaluation of Precipitation> The prepared polarizing film was observed and evaluated in the following manner using a Polarion clean room light manufactured by Polarion. Precipitation: Precipitation is visible when illuminated with a Polarion light No precipitation: No visible precipitates when illuminated with Polarion light

[0109] <Examples 2 to 9 and Comparative Examples 1 to 4> A polarizing film was produced in the same manner as in Example 1, except that a stretched polyvinyl alcohol film having a moisture content shown in Table 1 and a liquid containing a water-soluble compound shown in Table 1 were used, and the thickness of the coating liquid film was changed by adjusting the gravure rotation speed ratio and changing the cell capacity of the gravure roll. The obtained stretched polyvinyl alcohol film and polarizing film were used to carry out the above-mentioned evaluations. The results are shown in Table 1.

[0110] <Examples 10 to 13> A polarizing film was produced in the same manner as in Example 1, except that a stretched polyvinyl alcohol film having a moisture content shown in Table 1 and a liquid containing a water-soluble compound shown in Table 1 were used, the thickness of the coating liquid film was changed by adjusting the gravure rotation speed ratio and changing the cell volume of the gravure roll, and air was blown onto the coating surface at a wind speed of 2.5 m / s after coating the liquid containing the water-soluble compound (impregnation promotion step was performed). The obtained stretched polyvinyl alcohol film and polarizing film were used to carry out the above evaluations. The results are shown in Table 1.

[0111] <Example 14> A polarizing film was produced in the same manner as in Example 5, except that a polyvinyl alcohol film having a thickness of 30 μm was used, and the thickness of the coating liquid film was changed by adjusting the gravure rotation speed ratio and changing the cell capacity of the gravure roll. The obtained stretched polyvinyl alcohol film and polarizing film were used to carry out the above-mentioned evaluations. The results are shown in Table 1.

[0112] <Example 15, Comparative Example 5> A polarizing film was produced in the same manner as in Example 14, except that a stretched polyvinyl alcohol film having a moisture content shown in Table 1 and a liquid containing a water-soluble compound shown in Table 1 were used, and the thickness of the coating liquid film was changed by adjusting the gravure rotation speed ratio and changing the cell capacity of the gravure roll. The obtained stretched polyvinyl alcohol film and polarizing film were used to carry out the above-mentioned evaluations. The results are shown in Table 1.

[0113] <Example 16> As the thermoplastic resin substrate, an amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a long shape, a water absorption rate of 0.75%, and a Tg of about 75°C was used. One side of the resin substrate was subjected to a corona treatment. 13 parts by weight of potassium iodide was added to 100 parts by weight of a PVA-based resin obtained by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFYMER Z410") at a ratio of 9:1, to prepare a PVA aqueous solution (coating solution). The above PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60°C to form a PVA-based resin layer having a thickness of 13 μm, thereby manufacturing (preparing) a laminate. The obtained laminate was uniaxially stretched at free ends 2.4 times in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 130°C (air-assisted stretching process). Next, the laminate was immersed in an insolubilizing bath (aqueous solution with a boric acid concentration of 4.0% by weight) at 40°C for 30 seconds (insolubilizing process). Next, the laminate was immersed in a dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with respect to 100 parts by weight of water) at 30°C for 60 seconds while adjusting the concentration so that the polarizing film had a predetermined transmittance (dyeing process). Next, the laminate was immersed in a crosslinking bath (aqueous solution with a potassium iodide concentration of 3.0% by weight and a boric acid concentration of 5.0% by weight) at 40°C for 30 seconds (crosslinking process). After that, the laminate was immersed in a stretching bath (boric acid concentration of 4.0% by weight) at 70°C, and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching process). Thereafter, the laminate was immersed in a washing bath (aqueous solution with a potassium iodide concentration of 4.0% by weight) at 20°C to produce a laminate of stretched polyvinyl alcohol films containing water (washing treatment step). Furthermore, the laminate obtained by washing was gravure coated (conditions: honeycomb mesh pattern, 700 [lines / inch], cell volume 5 [cm]) in a state where the moisture content was 6.0% by weight. 3 / m 2

[0113] , gravure rotation speed ratio: 100%), an aqueous solution with a sodium chloride concentration of 5.0% by weight was applied to the resin substrate so that the thickness of the coating liquid film was 0.83 μm. The resin substrate was then dried for 10 minutes in an oven maintained at 95° C. (drying treatment step), to form a polarizing film with a thickness of 5 μm on the resin substrate. The obtained laminate of stretched polyvinyl alcohol films and the polarizing film were used to carry out the above evaluations. The results are shown in Table 1.

[0114] [Table 1]

Claims

1. A method for producing a polarizing film, comprising the steps of: A step (I) of producing a water-containing stretched polyvinyl alcohol-based film by carrying out at least a stretching step, a dyeing step, and a washing step while transporting the polyvinyl alcohol-based film in a longitudinal direction; a step (II) of applying a liquid containing a water-soluble compound to the obtained stretched polyvinyl alcohol-based film containing water while the stretched polyvinyl alcohol-based film has a moisture content of x% by weight (40≧x≧1.1×thickness (μm) of the stretched polyvinyl alcohol-based film) to produce a stretched polyvinyl alcohol-based film having a coating liquid film with a thickness of 0.3 μm or more and 2.2 μm or less; The method for producing a polarizing film includes a step (III) of drying the stretched polyvinyl alcohol film having the obtained coating liquid film thereon to produce a polarizing film.

2. 2. The method for producing a polarizing film according to claim 1, wherein in the step (II), the coating liquid film has coating unevenness of less than 0.1 μm.

3. 3. The method for producing a polarizing film according to claim 1, further comprising the step of: subjecting the stretched polyvinyl alcohol-based film having the obtained coating liquid film, in the step (III), to a step of promoting impregnation of the water-soluble compound, and then subjecting the stretched polyvinyl alcohol-based film having the obtained coating liquid film to a step of drying, thereby producing a polarizing film.

4. 4. The method for producing a polarizing film according to claim 3, wherein the step of promoting the impregnation of the water-soluble compound is performed before the stretched polyvinyl alcohol-based film transported after the step of applying the liquid containing the water-soluble compound comes into contact with a next transport roll.

5. 3. The method for producing a polarizing film according to claim 1, wherein in the step (III), the stretched polyvinyl alcohol-based film having the coating liquid film thereon is not subjected to a step of draining the coating liquid film.

6. A method for producing a polarizing film, comprising a step of laminating a transparent protective film via an adhesive layer to at least one surface of the polarizing film obtained by the method for producing a polarizing film according to claim 1 or 2.

Citation Information

Patent Citations

  • Polarizing film and its production

    JP1994172554A

  • Polarizer, its manufacturing method, polarizing plate, optical film and image display apparatus

    JP2006047978A

  • Polarizing plate, manufacturing method of polarizing plate, optical film and image display apparatus

    JP2008046257A

  • Manufacturing method and manufacturing device for polarizer

    JP2021009203A

  • Polarizer and production method therefor

    WO2016117659A1